PENINGKATAN KUALITAS PEMBELAJARAN IPA PADA MATERI SISTEM PENCERNAAN MANUSIA DENGAN STRATEGI JIGSAW-LESSON STUDY PADA SISWA KELAS VIII-A SMP NEGERI 3 PACITAN - Edi Winarno (Florea : Jurnal Biologi dan Pembelajarannya, 2014)
This study aims to improve the quality of science learning outcomes matter of human digestive system in class VIII-A of SMP Negeri 3 Pacitan school year 2011/2012 through the implementation of learning strategy Jigsaw - Lesson study. The results show that the quality of the science learning process increases . It can be seen from the increase in the percentage of success of the action on the first cycle of 62.59 % increased by 7.41% after the second cycle , which becomes 80.00 % and based on the level of success include the category very well . In addition it also increases the percentage of mastery learning in the time before the actions of 38.89 % , after the first cycle of 72.22 % and the second cycle in the classical mastery learning students reach 100 % . The average value of learning outcomes also increased , at the time before the action was 71.00 , after the first cycle of 72.31 and the second cycle in the classical mastery learning students achieve 76.31 . From the results of this study concluded that learning with LS - Jigsaw strategy can improve the quality of science teaching , the students of class VIII - A of SMP Negeri 3 Pacitan school year 2011/2012 .